Endemic architectural forms of Malabar and South Canara: The role of building material in shaping megaliths and temples: MEERA: MEGALITHS AND TEMPLES OF MALABAR AND SOUTH CANARA (Indian Journal of Traditional Knowledge (IJTK), 2025)
The strip of land constituting the regions of Malabar and South Canara along the western coast of India is renowned for unique architectural forms endemic to the region, including protohistoric megaliths and medieval temples. This paper argues that this propensity for architectural endemism is primarily due to the properties of locally available building materials – mainly laterite and timber, rather than the geographical isolation imposed by the Western Ghats and the Arabian Sea, as traditionally believed. The megaliths in this region, mostly from the Iron Age (1000BCE-500CE), and the medieval temples (800-1700CE), exhibit adaptations of the mainstream architectural traditions to suit the physical properties of laterite. This paper examines how architectural forms originally developed for construction using hard stone were re-interpreted to accommodate the properties of laterite. By analysing examples from both megalithic and temple contexts, it highlights the role of building material in determining the architectural identity of Malabar and South Canara.